ORGANIZATION OF MOBILE LEARNING AS A INNOVATION TECHNOLOGY IN EDUCATION - Tileubay, S.; Doszhanova, B.; Almenayeva, R.; Zharmenova, B.; Mussagulova, G. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
The authors, taking mobile learning as a promising vector of digital pedagogy, describe the advantages of using mobile learning technologies in the process of organizing the educational process and revealing the content of their mobile applications in the educational process. The article discusses the directions of using mobile learning in modern education, as well as the organization of mobile learning as an innovative technology in pedagogy. Today, mobile learning is a rapidly developing and promising area in education. Mobile technologies have made learning more flexible. It is noted that despite the wide distribution and availability of mobile phones among students, mobile learning is poorly distributed in domestic universities. It is concluded that the capabilities of mobile devices are constantly growing and they can be widely used as educational tools and take center stage in education.